Stabilizing Lithium Plating by a Biphasic Surface Layer Formed In Situ. Issue 31 (9th July 2018) - Pang, Quan; Liang, Xiao; Kochetkov, Ivan R.; Hartmann, Pascal; Nazar, Linda F.
Abstract: The dendritic growth of Li metal leads to electrode degradation and safety concerns, impeding its application in building high energy density batteries. Forming a protective layer on the Li surface that is electron‐insulating, ion‐conducting, and maintains an intimate interface is critical. We herein demonstrate that Li plating is stabilized by a biphasic surface layer composed of a lithium‐indium alloy and a lithium halide, formed in situ by the reaction of an electrolyte additive with Li metal. This stabilization is attributed to the fast lithium migration though the alloy bulk and lithium halide surface, which is enabled by the electric field across the layer that is established owing to the electron‐insulating halide phase. A greatly stabilized Li‐electrolyte interface and dendrite‐free plating over 400 hours in Li|Li symmetric cells using an alkyl carbonate electrolyte is demonstrated. High energy efficiency operation of the Li4 Ti5 O12 (LTO)|Li cell over 1000 cycles is achieved. Abstract : In you go : A micron thin, biphasic Li + ‐ion conductive protective film formed in situ in a battery on the Li metal surface results in dendrite‐free Li deposition in an alkyl carbonate electrolyte. The biphasic surface layer, composed of a lithium–indium alloy and a lithium halide, formed by the reaction of an electrolyte additive with Li metal.